Implementing the Main Circular Economy Principles within the Concept of Sustainable Development in the Global and European economy, with Particular Emphasis on Central and Eastern Europe - the Case of Poland and the Region of Lodz - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2018)
The aim of the article is to present the effects of selected activities implemented at the global, European and regional levels within the idea of sustainable development. Of particular importance here is the presentation of activities undertaken at the level of the Lodz region (one of the central regions of Poland) in which among 6 regional specializations, particular attention was paid to innovative organic farming and to the textile industry based on modern fashion and innovative design. All 6 specializations in the Lodz region, including medicine, pharmacy and the cosmetics industry, advanced building materials, electricity generation (including renewable energy sources), IT and telecommunications were directed to the implementation of the overarching bio-economy program aiming at achieving the main assumptions of the circular economy based on the 3Rs, i.e., "reduce, reuse, and recycle."
Keywords: O13; 330; sustainable development; bio-economy; circular economy; region of Lodz